Unlocking new horizons in oncology: ivonescimab’s dual-target approach to anti-VEGF/PD-1(L1) therapy - Shi, Fan; Yang, Luying; Gao, Ye; Hou, Yan; Lv, Qianxin; Cao, Feng; Chen, Xi; Zhang, Jianying; Wang, Le (Frontiers in Immunology, 2025)
Dual blockade of the PD-1/PD-L1 axis, enabling tumor immune evasion, and the VEGF pathway, driving immunosuppression, represents a promising cancer immunotherapy strategy. Combining immune checkpoint inhibitors (ICIs) with antiangiogenics faces toxicity and cost limitations. Bispecific antibodies (BsAbs) targeting both pathways offer a solution. Preclinical and clinical studies demonstrate that simultaneous inhibition enhances antitumor immunity by reversing T-cell exhaustion, normalizing vasculature, and countering immunosuppression. Ivonescimab, a first-in-class PD-1/VEGF BsAb, exemplifies this approach. Approved in China (NMPA, May 2024) for EGFR-mutant non-squamous NSCLC post-TKI failure and included in national insurance (November 2024), it is under global evaluation in solid tumors. PD-1(L1)/VEGF BsAbs like ivonescimab represent a novel therapeutic strategy with potential for improved efficacy and mitigated toxicity compared to combination therapies. Ongoing trials will define broader applications.